Corrosion and discharge performance of a magnesium aluminum eutectic alloy as anode for magnesium–air batteries. (1st July 2020) - Ma, Jingling; Zhang, Yi; Ma, Mingsheng; Qin, Conghui; Ren, Fengzhang; Wang, Guangxin
Graphical abstract: Highlights: Magnesium aluminum eutectic alloys are prepared as the anodes. Low corrosion rate of as-cast is due to aluminum-rich oxide in lamella β phase. Battery based as-cast and graphene compound has a good discharge performance. Abstract: Magnesium aluminum eutectic alloy (Mg–34 % Al) was prepared as anode of magnesium–air battery with a view to decrease the corrosion rate of magnesium anode. Results indicate that as–cast eutectic alloy has a lower corrosion rate and a lower discharge activity in 3.5 % NaCl solution. The assembled battery with as–cast eutectic alloy as anode, a water soluble graphene poly (sodium 4–styrenesulfonate)/graphene based NaCl solution and a graphene/Mn3 O4 nanometre composite as air cathode catalyst has a higher discharge activity. Lower corrosion rate of as–cast anode is due to corrosion products of black aluminum–rich oxide formed in fine lamella β–Mg17 Al12 phase.